The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1997
DOI: 10.1159/000111205
|View full text |Cite
|
Sign up to set email alerts
|

Connexin32 Gene Expression in Rat Sciatic Nerves and Cultured Schwann Cells

Abstract: A Western blot analysis showed connexin32 (Cx32) to be present in the myelin membrane. Cx32 mRNA rapidly decreased in the distal segments of crushed sciatic nerves and thereafter returned to normal, as did P0 mRNA. Both Cx32 and P0 mRNAs were detectable in cultured Schwann cells and were enhanced by the addition of forskolin. The developmental profile showed that Cx32 mRNA had thus markedly increased by the time that myelination had become most active, and thereafter only slowly increased unlike P0. Cx32 mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…In keeping with the proposed role as a candidate gene for CMTX, Cx32 is expressed at high levels in myelinating Schwann cells and is regulated in parallel to other myelin genes (Bergoffen et al, 1993;Scherer et al, 1995;Chandross et al, 1996b;Satake et al, 1997). Immunocytochemical studies have indicated that Cx32 is localized mainly in noncompacted domains of myelin, such as paranodal loops and SchmidtLanterman incisures (Bergoffen et al, 1993;Miyazaki et al, 1995;Scherer et al, 1995;Spray and Dermietzel, 1995;Chandross et al, 1996b;Nelles et al, 1996).…”
Section: Abstract: Gap Junction; Channel; Myelin; Schwann Cell; Neurmentioning
confidence: 69%
“…In keeping with the proposed role as a candidate gene for CMTX, Cx32 is expressed at high levels in myelinating Schwann cells and is regulated in parallel to other myelin genes (Bergoffen et al, 1993;Scherer et al, 1995;Chandross et al, 1996b;Satake et al, 1997). Immunocytochemical studies have indicated that Cx32 is localized mainly in noncompacted domains of myelin, such as paranodal loops and SchmidtLanterman incisures (Bergoffen et al, 1993;Miyazaki et al, 1995;Scherer et al, 1995;Spray and Dermietzel, 1995;Chandross et al, 1996b;Nelles et al, 1996).…”
Section: Abstract: Gap Junction; Channel; Myelin; Schwann Cell; Neurmentioning
confidence: 69%
“…Cx32 expression associated with adherens junctions in the paranodes and incisures has been previously described by a number of investigators (Bergoffen et al, 1993; Meier et al, 2004; Satake et al, 1997; Scherer et al, 1995; see also Arroyo and Scherer, 2000). Our observation that intense patches of IP 3 R3 ion channels are clustered in the same regions is intriguing.…”
Section: Discussionmentioning
confidence: 79%
“…2). Because the endogenous Cx32 mRNA is 1.6 kb (Satake et al, 1997;Yoshimura et al, 1996b), the 1.4 kb mRNA detected in Fig. 1 is thought to be the expression of the transfected genes.…”
Section: Resultsmentioning
confidence: 99%
“…In the peripheral nervous system (PNS), however, Cx32 is believed to be located in the myelin and to take part in intramyelin (intracellular) transport (Bruzzone et al 1994). Although studies of Cx32 expression in rat sciatic nerves and cultured Schwann cells showed that the pattern of Cx32 expression is similar to that of Po, a PNS myelin-specific protein (Scherer et al, 1995;Satake et al, 1997), immunoreactivity of Cx32, which is oberved at the regions of nodes of Ranvier and Schmidt-Lanterman incisures in PNS myelin (Bergofen et al, 1993;Miyazaki et al, 1995), is completely different from that of Po.…”
Section: Introductionmentioning
confidence: 99%